Conscription and the search for modern Russian Jewry - Litvak, Olga (The modern Jewish experience, 2006)
Russian Jews were first conscripted into the Imperial Russian army during the reign of Nicholas I in an effort to integrate them into the population of the Russian Empire. Conscripted minors were to serve, in practical terms, for life. Although this system was abandoned by his successor, the conscription experience remained traumatic in the popular memory and gave rise to a large and continuing literature that often depicted Jewish soldiers as heroes. This imaginative and intellectually ambitious book traces the conscription theme in novels and stories by some of the best-known Russian Jewish writers such as Osip Rabinovich, Judah-Leib Gordon, and Mendele Mokher Seforim, as well as by relatively unknown writers.